2017
DOI: 10.1007/s00248-017-1082-z
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Fatty Acid Production and Release in Benthic Algae: Could Parallel Allelopathy Be Explained with Plant Defence Theories?

Abstract: Many organisms produce chemical compounds, generally referred as secondary metabolites, to defend against predators and competitors (allelopathic compounds). Several hypotheses have been proposed to explain the interaction between environmental factors and secondary metabolites production. However, microalgae commonly use simple metabolites having a role in primary metabolism as allelopathic compounds. The aim of this study was to determine whether classical theories of plant chemical defences could be applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Allelopathy is considered as one of the factors promoting and maintaining the massive cyanobacterial and algal blooms in freshwater, brackish and marine ecosystems around the world [ 93 , 94 , 95 , 96 ]. Therefore, the number of reports about the allelopathic effects of different species of cyanobacteria and microalgae has been steadily increasing (e.g., [ 95 , 96 , 97 , 98 , 99 ]). However, only little information on picocyanobacterial allelopathy or their harmful effects on other organisms has been described ( Table 2 ).…”
Section: Allelopathic Activity Of Picocyanobacteria and Their Impamentioning
confidence: 99%
“…Allelopathy is considered as one of the factors promoting and maintaining the massive cyanobacterial and algal blooms in freshwater, brackish and marine ecosystems around the world [ 93 , 94 , 95 , 96 ]. Therefore, the number of reports about the allelopathic effects of different species of cyanobacteria and microalgae has been steadily increasing (e.g., [ 95 , 96 , 97 , 98 , 99 ]). However, only little information on picocyanobacterial allelopathy or their harmful effects on other organisms has been described ( Table 2 ).…”
Section: Allelopathic Activity Of Picocyanobacteria and Their Impamentioning
confidence: 99%
“…Other authors also observed that some cyanobacteria can cause allelopathy under non‐limiting nutrient conditions (Allen et al, ; Bittencourt‐Oliveira et al, ; Brutemark et al, ; Dias et al, ; Leflaive & Ten‐Hage, ). Allen et al () showed that allelopathic compounds produced by green algae Uronema confervicolum were the highest in the treatment with the highest nutrient level and were much lower in the unbalanced nutrients treatments. These results confirm the reports obtained on the same species and other green algae (Leflaive & Ten‐Hage, ).…”
Section: Discussionmentioning
confidence: 92%
“…One of the principal effects of eutrophication due to the anthropogenic supply of biogenic elements (especially nitrogen and phosphorus) is the excessive growth of phytoplankton. Recent studies suggest that the availability of nitrogen and phosphorus could affect cyanobacterial and microalgal allelopathy (Allen et al, ; Antunes et al, ) which, in turn, might be implied in the maintenance of harmful blooms (Figueredo, Giani, & Bird, ). Therefore, determining the effect of the increased availability of nutrients on the appropriate aspects should be a priority for present and future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the allelopathic effect can be influenced by abiotic factors, such as irradiation, temperature, and salinity. Uronema confervicolum (Chlorophyta) had a higher production of allelopathic compounds under higher light intensity (Allen et al 2017). The allelopathic effect is also temperature-dependent, as toxic Microcystis aeruginosa (Cyanobacteria) strains inhibited the growth of Chlorella vulgaris (Chlorophyta) more at high temperatures (≥ 25°C) (Ma et al 2015).…”
Section: Introductionmentioning
confidence: 99%